If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + X = -9 + 7 Combine like terms: -9 + 7 = -2 5 + X = -2 Solving 5 + X = -2 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + X = -2 + -5 Combine like terms: 5 + -5 = 0 0 + X = -2 + -5 X = -2 + -5 Combine like terms: -2 + -5 = -7 X = -7 Simplifying X = -7
| 13c+4=9c-20+c | | 37x-37=37x-37 | | 9X+6=16-32X+72 | | (x+12)=(20)-12 | | 74x-37=74x-37 | | 73x-37=73x-37 | | 0x-37=0x-37 | | 5(5x-5)+3x=-165 | | 5X+112=7X+105 | | 83x+-116=83x+116 | | x^2+3x+m=1 | | 1-5x=-8x+4 | | 6(1.3k-4.6)=11.4 | | 4-2y-y=12-4 | | 13x+11x+x=1520 | | 5x^2+2x=24 | | 0.7x-0.6(5-2x)=-0.9(x-6) | | 6x+8+3(m+2)=12.6 | | -6(y-2y)+2=-6(3y-y)+9+17y | | 7p+12=13+5p | | VAR(4-3Z)=0 | | x^5-x^4-2x^3+2x^2+24=0 | | Y=.50x-100 | | 4z-a=3 | | y=x^9/x^13 | | 12/5(r-2)=2/3(3r-2(2r-1)) | | y=(7x-1)(x+3) | | y=(7x+1)(x-3) | | -3(y-4)=-5(y+2) | | x=(7x+1)(x-3) | | 5*4/8*-1/-7= | | 8y+6=-y-2 |